The impact of hypoxia on nephrogenesis - Buchholz, Björn; Schley, Gunnar; Eckardt, Kai-Uwe (Current Opinion in Nephrology and Hypertension, 2016)
Purpose of reviewKidney development depends on outgrowth of the ureteric bud into the metanephric mesenchyme. The number of ureteric bud branching events determines the final number of nephrons, which correlates inversely with the risk for development of chronic kidney disease and arterial hypertension during lifetime. The purpose of this review is to highlight the influence of oxygen on nephrogenesis and to describe cellular mechanisms by which hypoxia can impair nephron formation.Recent findingsAlthough kidney development normally takes place under hypoxic conditions, nephrogenesis is impaired when oxygen availability falls below the usual range. Hypoxia-inducible factors (HIF) play an important role in linking low oxygen concentrations to the biology of nephron formation, but their effect appears to be cell type dependent. In ureteric bud cells, HIF stimulates tubulogenesis, whereas HIF stabilization in cells of the metanephric mesenchyme results in secretion of growth factors, including vascular endothelial growth factor A, which in aggregate inhibit ureteric bud branching. The balance between pro and antibranching effects may be altered in various ways, but the inhibitory effect usually seems to predominate under reduced oxygen concentrations, explaining how intrauterine hypoxia can lead to low nephron numbers.SummaryOxygen availability has a complex influence on nephrogenesis. Oxygen concentrations outside an optimal low range may affect nephron endowment. Associations between placental insufficiency and increased risk for chronic kidney disease and arterial hypertension during later life may to a large extent be due to direct effects of reduced oxygen supply to the metanephric mesenchyme and mediated through the HIF pathway.
Keywords: chronic kidney disease; hypoxia; hypoxia-inducible factor-1 alpha; kidney development; nephron number